A structural study of mercury adsorbed on single crystal metal surfaces - Bastow, Sarah Louise (1997)
The Normal Incidence X-Ray Standing Wavefield technique has been used to study the adsorption of mercury on two single crystal metal surfaces, Ni(111) and Cu(100). The three Hg/Ni(111) structures studied were (√3x√3)R30°-0.33ML, p(2x2)-0.SML and "c(2√3x2√3)R30°"-0.64ML. A well-ordered, commensurate mercury adlayer is postulated, which has a low frequency (or soft) phonon mode parallel to the surface. Such a surface is well ordered and will give good LEED patterns, but the large distribution of distances relative to the (111) set of planes leads to a low coherent fraction, in agreement with the (111) NIXSW data. The Hg/Cu(100) structures studied were two equilibrium structures, c(2x2)-0.SOML and c(4x4)-0.62ML and two nonequilibrium structures, (3x3)-0.66ML and c(2x6)-0.83ML. In agreement with the literature, the NIXSW analysis of the lowest coverage Cu(100)/Hg-c(2x2)-0.SOML structure indicated mercury adsorption into the most energetically stable four-fold hollow sites. However, the NIXSW analysis of the Cu(100)/Hg-c(4x4)-0.62ML structure appears to disprove the mercury coincidence net proposed by previous authors. Our model proposes that some of the mercury atoms adsorb exactly in energetically favourable four-fold hollow sites whilst some reside in sites slightly off the four-fold hollow position. The Cu(100)/Hg-(3x3)-0.66ML structure is found to consist of two domains, each containing mercury atoms adsorbed equally in both bridge and four-fold hollow sites and differing only in the type of bridge sites occupied by the mercury adsorbate atoms. Finally, the NIXSW data of the highest coverage Cu(100)/Hg-c(2x6)-0.83ML structure, was found to indicate a model combining a slightly rumpled overlayer with more than a monolayer of adsorbate atoms to fit the experimental NIXSW data presented here.